Hai på menyen - Leif Inge Åstveit (Viking, 2023)
In 2021 the University Museum of Bergen conducted an archaeological excavation at the Middle Neolithic (3500–2700 BC) site Nerlandsøy at Sunnmøre. The most surprising find was 154 teeth from Porbeagle shark (Lamna nasus) imbedded in culture layers. Teeth from this species have been found in three other sites infrom North-Western Norway, however in much lesser number than on Nerlandsøy. In this paper the shark teeth are interpreted as a hitherto unknown part of the increasing big game hunting taking place in the Middle Neolithic. The hunting activity is reflected both in the material culture, as well as in the rock art, in the region and is believed to be an important part of the social dynamics of the society.